2020
DOI: 10.3389/fvets.2020.00175
|View full text |Cite
|
Sign up to set email alerts
|

Colder Ambient Temperatures Influence Acute Onset Canine Intervertebral Disc Extrusion

Abstract: Canine intervertebral disc disease is one of the most common neurologic conditions in veterinary medicine but the influence of environmental factors thereon has not been fully investigated. Subjectively, there has been the impression of increased admissions of acute spinal cord injuries due to intervertebral disc extrusion during periods of colder temperatures. In the present retrospective study, the different weather conditions (temperature, precipitation, sunshine, humidity, and atmospheric pressure) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Since IVDD has a multifactorial etiology, the collection of a wide range of further information, including other anatomical and morphological risk factors found in previous studies would be necessary. Furthermore, environmental influencing factors, activity level and occupation of the patient (working dog) should be included in the assessment of the real risk of IVDD for a specific patient ( 51 ). It would also be interesting to analyse if there are differences within chondrodystrophic breeds that have different vertebrae conformations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since IVDD has a multifactorial etiology, the collection of a wide range of further information, including other anatomical and morphological risk factors found in previous studies would be necessary. Furthermore, environmental influencing factors, activity level and occupation of the patient (working dog) should be included in the assessment of the real risk of IVDD for a specific patient ( 51 ). It would also be interesting to analyse if there are differences within chondrodystrophic breeds that have different vertebrae conformations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These differences reflect preferences for standard or miniature and variable hair characteristics in different countries. Risk factors including neuter status ( 45 , 50 ), physical conformation ( 44 , 47 50 ), axial muscle fascicle length ( 65 ), ambient temperature ( 66 ), hair characteristics ( 47 , 50 ), and exercise ( 46 , 50 ) have been reported with variable consistency in findings across studies.…”
Section: What We Don't Knowmentioning
confidence: 99%
“…Most dogs were admitted in the months of February, March, April, and May, followed by the autumn and winter months, when the ambient temperature tends to be lower. This is leading to spasms and changes in biomechanical forces [ 8 ], but the lower occurence may also be due to the fact that most people spend vacations during summer and warm months, and therefore, the number of recorded cases in dogs is lower. The effect of temperature on the occurrence of intervertebral disc disease observed in this study is also found in some human studies on a number of diseases, where lower ambient temperatures are associated with more pain in conditions such as osteoarthritis, pelvic pain syndrome, and musculoskeletal pain, and may also increase the risk of muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…In another study regarding dogs by Barandun et al (2020), the authors described the effect of cold temperatures on the mobility of the musculoskeletal system, whereas it also notably affected the spinal column. With both reduced mobility and resistance to strain injuries, biomechanical forces could act differently or more traumatically on the spine, although this is purely speculative [ 8 ].…”
Section: Introductionmentioning
confidence: 99%